ANALISIS NILAI-NILAI PROFIL PELAJAR PANCASILA DALAM CERITA RAKYAT LEGENDA BATANG PAING KUANTAN SINGINGI - Ningtyas, Afrilia; Ningsih, Rika (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2026)
Education in the era of globalization in Indonesia faces challenges in maintaining national identity while simultaneously shaping a young generation with strong character and competitiveness. One effort to address this challenge is through strengthening the values of the Pancasila Student Profile. This study aims to analyze the values of the Pancasila Student Profile contained in the folklore Legenda Batang Paing Kuantan Singingi. This research employs a qualitative approach using the content analysis method. The data source is the text of the folklore, while the research data consist of phrases, sentences, and quotations that reflect the six dimensions of the Pancasila Student Profile. Data analysis techniques include determining research focus, coding, calculating the frequency of value occurrences, data presentation, and drawing conclusions. The findings indicate that all dimensions of the Pancasila Student Profile are present in the folklore. The value of faith in and devotion to Almighty God appears most dominantly, reflecting the strong religiosity and moral values of the local community. The values of mutual cooperation and independence emerge with moderate intensity through the actions of the main character in helping others and facing life challenges. Meanwhile, the values of global diversity as well as critical and creative reasoning appear in a smaller proportion, mainly through attitudes of respecting traditions, decision-making, and adaptability to the environment. These findings demonstrate that Legenda Batang Paing Kuantan Singingi not only contains general character values but also represents a hierarchy of Pancasila Student Profile values that are relevant as a source of character education based on local wisdom.